Varied origins of the Irish people - Sadleir, T.U. (Statistical and Social Inquiry Society of Ireland, 1933)
The study of genealogy is based on the investigation of surnames.
Read on Friday, 21st April, 1933
Keywords: Population migration; Irish names; 314.15